TMET-32. INTRAOPERATIVE MICRODIALYSIS FOR GLIOMA METABOLIC RECONNAISSANCE AND BIOMARKER DISCOVERY. (14th November 2022) - Riviere-Cazaux, Cecile; Carlstrom, Lucas; Rajani, Karishma; Munoz-Casabella, Amanda; Rahman, Masum; Burns, Terry
Abstract: Gliomas are genomically heterogeneous tumors that may harness a convergent and therapeutically targetable set of metabolic pathways. At present, the metabolic landscape of in situ human gliomas remains incompletely characterized, hampering translational progress. To that end, we are leveraging the previously untapped potential of high molecular weight microdialysis to determine the global extracellular metabolic profiles of live human gliomas. Under an investigational device exemption, HMW microdialysis (< 100 kDa) was performed at 2.0 μL/min in an initial discovery cohort of five patients in glioma and adjacent brain during neurosurgical resection; a subsequent cohort of five patients was independently analyzed to critically evaluate results from the discovery group. Untargeted metabolomics via ultra-performance liquid chromatography-tandem mass spectrometry revealed over 300 named metabolites and five drugs from only 20 μL of microdialysate, representing a short and feasible 10 minutes of intraoperative collection time. Enrichment analysis of each patient's tumor vs. brain ranked extracellular metabolome highlighted marked metabolic convergence within the most aggressive regions of molecular diverse tumors (FDR = 0). Pathway analysis revealed significant enrichment for large neutral amino acid pathways, including valine, leucine, and isoleucine biosynthesis (p=1.6E-9) and degradation (p=0.001) and glycine, serine, and threonine metabolism (p=4.7E-5). Notably, this amino acid signature was not as abundantly present in nonenhancing tumor when compared to enhancing tumor (Average tumor/brain: 1.9x vs. 4.3x, respectively), suggesting upregulation of neutral amino acid transporters in enhancing tumor or delivery from plasma into the CNS via a disrupted BBB. Interestingly, guanidinoacetate (GAA) was our most highly conserved and upregulated metabolite (128.9x in tumor vs. brain). Given its co-production with ornithine, the precursor to protumorigenic polyamines, we posit that GAA may serve as a biomarker of increased ODC activity in live human gliomas. In conclusion, intraoperative HMW microdialysis feasibly offers improved opportunities to perform glioma metabolic biomarker and therapeutic discovery.